A systematic review of barriers and facilitators to antenatal screening for HIV, syphilis or hepatitis B in Asia: Perspectives of pregnant women, their relatives and health care providers. - Lucie Sabin; Hassan Haghparast-Bidgoli; Faith Miller; Naomi Saville (PLoS ONE, 2024)
Background Despite improvements, the prevalence of HIV, syphilis, and hepatitis B remains high in Asia. These sexually transmitted infections (STIs) can be transmitted from infected mothers to their children. Antenatal screening and treatment are effective interventions to prevent mother-to-child transmission (MTCT), but coverage of antenatal screening remains low. Understanding factors influencing antenatal screening is essential to increase its uptake and design effective interventions. This systematic literature review aims to investigate barriers and facilitators to antenatal screening for HIV, syphilis, and hepatitis B in Asia. Methods We conducted a systematic review by searching Ovid (MEDLINE, Embase, PsycINFO), Scopus, Global Index Medicus and Web of Science for published articles between January 2000 and June 2023, and screening abstracts and full articles. Eligible studies include peer-reviewed journal articles of quantitative, qualitative and mixed-method studies that explored factors influencing the use of antenatal screening for HIV, syphilis or hepatitis B in Asia. We extracted key information including study characteristics, sample, aim, identified barriers and facilitators to screening. We conducted a narrative synthesis to summarise the findings and presented barriers and facilitators following Andersen's conceptual model. Results The literature search revealed 23 articles suitable for inclusion, 19 used quantitative methods, 3 qualitative and one mixed method. We found only three studies on syphilis screening and one on hepatitis B. The analysis demonstrates that antenatal screening for HIV in Asia is influenced by many barriers and facilitators including (1) predisposing characteristics of pregnant women (age, education level, knowledge) (2) enabling factors (wealth, place of residence, husband support, health facilities characteristics, health workers support and training) (3) need factors of pregnant women (risk perception, perceived benefits of screening). Conclusion Knowledge of identified barriers to antenatal screening may support implementation of appropriate interventions to prevent MTCT and help countries achieve Sustainable Development Goals' targets for HIV and STIs.